2004
DOI: 10.1021/jp037401w
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Route Graphs. II. Examples of Enzyme- and Surface-Catalyzed Single Overall Reactions

Abstract: The utility of the new reaction route (RR) graph theory developed in the preceding paper (Part I) is illustrated here, with the help of two examples. In the first example, the kinetics of the conversion of 7,8-dihydrofolate and NADPH to 5,6,7,8-tetrahydrofolate and NADP, as catalyzed by dihydrofolate reductase (DHFR), is considered. This system is described by a linear kinetic mechanism that includes 13 elementary reaction steps. The second example is a microkinetic model of the water-gas shift reaction on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…36 This may be accomplished by appropriately combining the elementary steps into the so-called intermediate reactions (IR). [41][42][43] There are different ways in which the Campbell's DRC, once hence numerically computed for all the steps in a microkinetic model, may be utilized for identification of key steps and model reduction. 46 One such method is the so-called principal component analysis, 40,47,48 in which the eigenvalues and eigenvectors of the matrix X T X are computed.…”
Section: Parametric Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…36 This may be accomplished by appropriately combining the elementary steps into the so-called intermediate reactions (IR). [41][42][43] There are different ways in which the Campbell's DRC, once hence numerically computed for all the steps in a microkinetic model, may be utilized for identification of key steps and model reduction. 46 One such method is the so-called principal component analysis, 40,47,48 in which the eigenvalues and eigenvectors of the matrix X T X are computed.…”
Section: Parametric Sensitivity Analysismentioning
confidence: 99%
“…53 In other words, one needs both thermodynamic (affinity, or reversibility) and kinetic (resistance) characteristics of a reaction step to judge its significance in the overall scheme of things. The electrical network analogy based on the RR graph approach [41][42][43] incorporates both of these aspects. It, thus, comprehensively incorporates and illuminates the network structural constraints embodied by the two Kirchhoff's laws (mass balance, and Hess's law) described below, which further ascribe to reaction networks a complete and quantitative correspondence to electrical networks.…”
Section: Electrical Analogy and Reaction Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirchhoff graphs were so-named because they satisfy both the Kirchhoff potential law and the Kirchhoff current law. The use of Kirchhoff graphs as reaction network diagrams was discussed by Fehribach [1], as well as by Fishtik, Datta et al [3][4][5][6], who discuss a related graph, the "reaction route graph". A number of other graphs have been used in the study of reaction networks; a summary can be found in [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This theory could be applied to various types of networked systems previously examined with other methods, such as plant-wide (integrated) process networks (Luyben et al, 1999), (Hangos et al, 1999), (Gilles, 1998), (Kumar & Daoutidis, 2002), chemical reaction networks (Fishtik et al, 2004), or biological networks (Majewski & Domach, 1989), (Hatzimanikatis et al, 1996).…”
Section: Introductionmentioning
confidence: 99%